A Model Curriculum for an Emergency Medical Services (EMS) Rotation for Emergency Medicine Residents - Michael Mancera; Aaron Kraut; Megan Gussick; Michael Lohmeier (eScholarship Publishing, University of California, 2018)
Audience: This EMS curriculum is designed for Emergency Medicine residents at all levels of training. Introduction: Emergency Medicine (EM) physicians have routine interaction with Emergency Medical Services (EMS) in their clinical practice. Additionally, the American College of Graduate Medical Education (ACGME) mandates that all Emergency Medicine resident physicians receive specific training in the area of EMS.1 Historically, EMS training for EM residents has been conducted in the absence of a standardized didactic curriculum. Despite advancements in the area of prehospital training, there remains wide inconsistency in EMS training experiences among EM residency training programs.2 To our knowledge a standardized and reproducible EMS curriculum for EM residents does not exist. Objectives: The aim of this curriculum is to provide a robust learning experience for EM residents around prehospital care and EMS that fulfills the ACGME requirements and which can be easily replicated and implemented in a variety of EM residency training programs. Method: The educational strategies used in this curriculum include didactics, asynchronous learning through online modules and a focused reading list, experiential learning through ride-alongs, structured small group discussion, supervised medical command shifts, and mentored practice in organizing and delivering didactics to EMS providers.